2021
DOI: 10.1186/s12984-021-00903-6
|View full text |Cite
|
Sign up to set email alerts
|

Sequential motor learning transfers from real to virtual environment

Abstract: Background Skill acquisition of motor learning between virtual environments (VEs) and real environments (REs) may be related. Although studies have previously examined the transfer of motor learning in VEs and REs through the same tasks, only a small number of studies have focused on studying the transfer of motor learning in VEs and REs by using different tasks. Thus, detailed effects of the transfer of motor skills between VEs and REs remain controversial. Here, we investigated the transfer o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…We believe that our findings may provide an important information for further understanding the relationship between body ownership and agency. In addition, our results, in particular, the increase in agency of the inactive hand by a simple action of the active hand may be helpful in studies on, for instance, rehabilitation of upper limb hemiplegia [52], phantom pain, and chronic pain in which the patients lose the normal ability to move or aware their hand. Further studies with VR-based platforms like our experimental system may provide novel and effective medical treatments to those diseases or disorders.…”
Section: Discussionmentioning
confidence: 61%
“…We believe that our findings may provide an important information for further understanding the relationship between body ownership and agency. In addition, our results, in particular, the increase in agency of the inactive hand by a simple action of the active hand may be helpful in studies on, for instance, rehabilitation of upper limb hemiplegia [52], phantom pain, and chronic pain in which the patients lose the normal ability to move or aware their hand. Further studies with VR-based platforms like our experimental system may provide novel and effective medical treatments to those diseases or disorders.…”
Section: Discussionmentioning
confidence: 61%
“…The movement patterns of RW and VR were different in this study (22). Investigation of the transfer of sequential motor learning indicated that the sequential reaching task in VR environments was facilitated after the sequential finger task in RW environments (23). Participants who train in the RW environment have an improvement in motor performance when they transfer to the VR environment.…”
Section: Introductionmentioning
confidence: 65%
“…Systematic reviews express that weaker research showed larger effects in favor of VR training than RW (18), and less VR allows participants to gain experience in learning the structure of skills (19). Participants who trained sequential motor tasks in the RW environment have an improvement when they transferred to the VR environment (23,24). In contrast, participants who train in the VR environment show a decrease in skill level when transferring to the RW environment (24).…”
Section: Performance Outcomesmentioning
confidence: 96%
“…If this interpretation is true, then cognitive load may have the strongest affects early in the motor learning process. Motor learning in the real world has been shown to facilitate subsequent motor learning processes in HMD-VR, suggesting that HMD-VR may be more effectively used in later stages of motor learning [ 38 ]. Thus, initial training done without the use of HMD-VR may then increase the effectiveness of HMD-VR applications.…”
Section: Discussionmentioning
confidence: 99%